Prompt diagnosis and management of Epstein–Barr virus‐associated post‐transplant lymphoproliferative disorder and hemophagocytosis: A dreaded complication in a post‐liver transplant child. (15th July 2015) - Jha, Bhawna; Mohan, Neelam; Gajendra, Smeeta; Sachdev, Ritesh; Goel, Shalini; Sahni, Tushar; Raina, Vimarsh; Soin, A
Abstract EBV‐associated PTLD is increasingly recognized as an important cause of morbidity and mortality in both solid organ and hematopoietic stem cell transplant recipients. Mortality rates due to PTLD and virus‐induced HLH are reported to be quite high. We report a case of EBV‐associated PTLD and HLH in a child after liver transplantation who was successfully managed due to timely intervention. This case highlights that measurement of EBV load by quantitative polymerase chain reaction assays is an important aid in the surveillance and diagnosis of PTLD and early detection of EBV‐induced PTLD, and aggressive treatment with rituximab is a key to survival in patients who have undergone liver transplantation.